التوحيد: رؤية للكون وإبستمولوجيا بناء الوعي المتجاوز عند إسماعيل راجي الفاروقي - الحاج دواق (International Institute of Islamic Thought, 2013)
تميّز إسماعيل الفاورقي بحيازته لأدوات النظر والاجتهاد، وأساليب الفهم والتحليل والتفسير، نتيجة استيعابه للمعرفة والثقافات الروحية التي رسختها الأديان في العالم، واستيعابه للفلسفات الغربية المعاصرة. وتوصل إلى أن التوحيد الذي يقدمه الإسلام هو جوهر التجربة الدينية، وقد تجاوز الفاروقي المعنى المتوارث للتوحيد؛ إلى الوجه الحضاري للرؤية التوحيدية، وتجلياتها في الوجود، والمعرفة، والقيم، وأنظمة الحياة. Ismail al-Faruqi was known by possessing the tools of vision and Ijtihad, and the methods of understanding, analysis, and interpretation. He has accomplished this status as a result of comprehending spiritual knowledge and cultures instilled by religions throughout the world, and through his comprehension of contemporary Western philosophies. Al-Faruqi concluded that Tawhid, as presented by Islam, is the essence of religious experience.  He transcended the inherited meaning of Tawhid to reach the civilizational aspect of the Tawhidic worldview and its manifestations in existence, knowledge, values, and systems of life.